(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: Early diagnosis of clinical chorioamnionitis (ChAm) in patients with premature rupture of membrane (PROM) is essential for its prompt treatment with antibiotics. Amniocentesis may be used to detect subclinical infections in cases of PROM. But the procedure is an invasive one. The present study was undertaken to study the role of plasma C-reactive protein (CRP) in the prediction of clinical chorioamnionitis in case of PROM. Materials & Methods The cross-sectional study was carried out in the of Departments of Obstetrics & Gynaecology, Khulna Medical College Hospital, Khulna over a period 1 year from July 2014 to June 2015. A total of 90 clinically diagnosed cases of PROM (rupture of the membrane with release of the amniotic fluid more than 1 hour prior to the onset of labor) were consecutively included in the study based on predefined enrolment criteria. Clinical ChAm is defined by findings such as leukocytosis [WBC count, >15,000/µL, fetal tachycardia, maternal fever (temperature, >100.4°F), fundal or uterine tenderness, or foul-smelling amniotic fluid]. A CRP value of > 10 mg/L was considered as raised or positive CRP. The risk of developing clinical ChAm in patients with raised CRP was then estimated by computing the Odds ratio. Result: The mean age of the women with PROM was 23.9 years. The patients presented with fundal or uterine tenderness (10%), raised maternal temperature (8.9%), foetal tachycardia (10%), maternal tachycardia (13.3%), foul smelling amniotic fluid (6.7%). Over half (52.2%) of the patients were preterm PROM and the rest were term PROM. Positive CRP was found in 16.7% cases. Raised WBC count and raised ESR were found in 11.1 and 33.3% cases respectively. Over two-thirds (70%) who developed clinical chorioamnionitis had raised CRP as opposed to 10% of those who did not develop the condition. The risk of having raised CRP in patients who developed clinical chorioamnionitis was > 20-fold (4.5 - 97.7) higher than those who did not develop the condition (p < 0.001). The sensitivity and specificity of CRP in diagnosing and ruling out chorioamnionitis respectively in cases of PROM were 70% and 90% respectively. The positive and negative predictive values of the test are 46.7% and 96% respectively. Conclusion: The study concluded that a substantial proportion of the PROM cases with clinical chorioamnionitis is manifested with raised CRP compared to PROM cases without chorioamnionitis. However, CRP is moderately sensitive to diagnose chorioamnionitis and highly specific to rule out the condition in cases with PROM. Ibrahim Cardiac Med J 2014; 4(2): 26-31